Habitat geometry and limited perceptual range affect habitat choice of a trap-building predator. (10th April 2018) - Katz, Noa; Scharf, Inon
Abstract : Density has been considered as the main force dictating how animals choose where to settle. We show that density has contrasting effects on this decision, based on habitat shape and not only area. This finding has not been considered in any of the theoretical models predicting habitat choice by animals in nature. Animals are limited by different physiological or morphological constraints and it is important to adjust existing models to the species under study. Abstract: By considering various biotic and abiotic factors, organisms are expected to distinguish among suitable habitats of different quality and choose the one that offers them the highest fitness payoff. According to the ideal-free-distribution model, density drives organism choice and ultimately distribution among habitats. However, deviations from the basic model are common, as it does not take into account intrinsic and extrinsic constraints. Two important constraints are those of habitat geometry (e.g. habitat area, habitat shape), and perceptual range. We used a trap-building predator, the wormlion larva, to examine these constraints. We manipulated the geometry of the preferred shaded microhabitat and the distance of individuals from it, and assessed their effect on wormlion habitat choice, distribution patterns, and performance. Habitat geometry affected wormlion microhabitat choice and distribution patterns, measured as distance from the habitat center and spatial pattern type, but had no effect on performance, expressed as the area of the pit-trap constructed. The interaction between habitat geometry and density was inconsistent regarding the distribution patterns, affecting distance from the center but not the spatial pattern type. Furthermore, we found that wormlions demonstrated a low perceptual range, which limited their ability to sense proximate shaded conditions. We highlight the importance of incorporating the interplay between habitat geometry, density, and perceptual range when studying habitat choice and spatial patterns and suggest that spatial patterns should be analyzed in more than a single way.